RELEVANSI KONSEP THEOS DARI ARISTOTELES DENGAN GENGGONALANGI SEBAGAI KEKUATAN SPIRITUAL MASYARAKAT NUSA UTARA - Dandel, Fredrik; Harianto, GP; Arifianto, Yonatan Alex (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2024)
This study aims to explore the relevance of the concept of God in Western philosophy by Aristotle with the local concept of God among the people of North Nusa, known as Genggonalangi. According to Aristotle, Theos or God is the Unmoved Mover, the source of all motion in the universe. This concept aligns with the understanding of Genggonalangi as the supreme supernatural power. The study employs a qualitative descriptive method through literature review and interviews. The findings reveal parallels between Theos and Genggonalangi: (1) awareness of a mysterious sacred power rooted in thought, (2) God as a Pure Act without material form, (3) God as the Supreme Ruler, and (4) spiritual power as the foundation of human life. This study opens opportunities for further research on integrating local spiritual values with Christian teachings within the cultural context of North Nusa.